The Relationship Between Knowledge and Diet Against the Incidence of Diabetes Mellitus at Dr. Suzie B.A.S Clinic Ciputat Tangerang Selatan - Iin Nurjana Far Far; Al Asyary (UHAMKA Press, 2019)
Diabetes mellitus has been the cause of 4.6 million deaths. The International Diabetes Federation (IDF) estimates that as many as 183 million people are unaware that they have DM. Based on preliminary study conducted by researchers, about 50% of patients who went to the dr. Suzie B.A.S Clinic suffers from diabetes mellitus.The purpose of this research is to find out the correlation between knowledge and diet to the case of diabetes mellitus in dr. Suzie B.A.S Clinic Ciputat Tangerang Selatan 2017.The type of this research is analytical with cross sectional appoarch. This research’s variable are knowledge and diet. The data used are primary data based on interview result using questionnaire. Secondary data sourced from examination sheet of diabetes melitus. The number of population are 1.988 with sample 0f 114 respondents. The technique of collecting samples with quota sampling method. The analysis used is univariate and bivariate analysis (chi square). Univariate test results showed that 20.2% of respondents had diabetes mellitus, had knowledge of diabetes mellitus 28,9% bad, and 47,4% respondent had bad diet. In addition there is a significant correlation between the case of diabetes mellitus with knowledge (Pvalue = 0.013) with PR 2,678, while dietary variables are not associated with the case of diabetes mellitus (Pvalue = 0.603) with PR 1,313. This research suggests that Clinic can improve service to patient, especially giving education to patient of diabetes mellitus so that patient better understand about understanding, symptom, and factors causing diabetes mellitus, especially education about diet which can become one of the most influencing factor of the happening of diabetes melitus.